Spatial Modeling of Flood Prone Areas in Huamual Sub-district Seram Bagian Barat Regency Indonesia - Rakuasa, Heinrich (PT. Pubsains Nur Cendekia, 2023)
Modeling of flood-prone areas is needed to provide information as an initial step in future flood disaster mitigation efforts. This research aims to spatially analyze the level of flood vulnerability and affected settlements in the Hunimual Sub-district. The method used is Multi-Criteria Analysis (MCA) by weighting the value of each variable. The variables that influence flooding in this study consist of land elevation, slope, land cover, distance from the river, geology, and rainfall. The determination of weights and scores in this study is an expert judgment. The weighting results are then overlaid to obtain a flood vulnerability map. The results show that the level of flood vulnerability is dominated by the very low vulnerability level of 69.09%, low vulnerability of 22.50%, and high vulnerability of 8.41% of the total area of the research location. The area of settlements affected by flooding is 556.47 ha. The results of this study are expected to be used as a basis for future flood disaster mitigation efforts to minimize losses, both casualties and physical damage in Hunimual District